Adults at high-risk of severe coronavirus disease-2019 (Covid-19) in Brazil - Rezende, Leandro F. M.; Thome, Beatriz; Schveitzer, Mariana Cabral; Souza-Júnior, Paulo Roberto Borges de; Szwarcwald, Célia Landmann (Revista de Saúde Pública, 2020)
OBJECTIVE: To estimate the proportion and total number of the general adult population who may be at higher risk of severe Covid-19 in Brazil. METHODS: We included 51,770 participants from a nationally representative, household-based health survey (PNS) conducted in Brazil. We estimated the proportion and number of adults (≥ 18 years) at risk of severe Covid-19 by sex, educational level, race/ethnicity, and state based on the presence of one or more of the following risk factors: age ≥ 65 years or medical diagnosis of cardiovascular disease, diabetes, hypertension, chronic respiratory disease, cancer, stroke, chronic kidney disease and moderate to severe asthma, smoking status, and obesity. RESULTS: Adults at risk of severe Covid-19 in Brazil varied from 34.0% (53 million) to 54.5% (86 million) nationwide. Less-educated adults present a 2-fold higher prevalence of risk factors compared to university graduated. We found no differences by sex and race/ethnicity. São Paulo, Rio de Janeiro, Minas Gerais, and Rio Grande do Sul were the most vulnerable states in absolute and relative terms of adults at risk. CONCLUSIONS: Proportion and total number of adults at risk of severe Covid-19 are high in Brazil, with wide variation across states and adult subgroups. These findings should be considered while designing and implementing prevention measures in Brazil. We argue that these results support broad social isolation measures, particularly when testing capacity for SARS-CoV-2 is limited.